In- vitro regeneration of an important medicinal plant Centella asiatica L. Urban - Jaheduzzaman, Dr; Habib, MA; Akter, S; Banu, NA; Rahman, RB; Banu, TA; Khan, S; Islam, S (Bangladesh Journal of Scientific and Industrial Research, 2012)
An in vitro multiple shoot regeneration protocol has been developed for Centella asiatica L. Urban from the nodal and shoot tips explants using MS medium with different concentrations and combinations of growth regulators. Multiple shoot regeneration was observed from both the explants on MS containing either BAP alone or in combination with IAA, NAA and Kn. Of the two explants, nodal segment showed comparatively better response towards multiple shoot regeneration. Maximum multiple shoots were found on MS supplemented with 1.0 mg/L BAP and 0.4 mg/L NAA. For root induction, well-developed shoots were excised and cultured on both MS and half strength of MS with various concentrations of IBA, IAA and NAA. Profuse healthy rooting was obtained on MS medium containing 0.2 mg/L IBA. The well rooted plantlets were successfully transplanted to the garden soil and their survival rate under natural condition was 90-95 %. DOI: http://dx.doi.org/10.3329/bjsir.v47i3.13058 Bangladesh J. Sci. Ind. Res. 47(3), 269-272, 2012